Corrosion in Mg-alloy biomedical implants- the strategies to reduce the impact of the corrosion inflammatory reaction and microbial activity - Saha, Soumya; Lestari, Widya; Dini, Caroline; Sarian, Murni Nazira; Hermawan, Hendra; A.R.Barão, Valentim; Sukotjo, Cortino; Takoudis, Christos (KeAi Chinese Roots Global Impact (Science Direct), 2022)
The most common complication of orthopedic surgery is implant failure, which can result in catastrophic injury and a significant financial burden for patients. Implant failure can be caused by a variety of factors, the most common of which are peri–implant infection (or implantrelated infection), excessive inflammatory response which caused pain and aseptic loosening. Orthopedic surgeons now have a variety of options for treating these issues, including revision surgery, which has demonstrated to be effective. If excessive inflammatory reaction caused by the corrosion and peri–implant infection can be avoided, it will be of enormous social benefits. This review will provide a summary of corrosion and the inflammation reactions due to the corrosion and antimicrobial properties of Mg alloy-based implants covering both in vitro and in vivo studies. The strategies on hindering/overcoming the excessive inflammatory response and enhancing the antimicrobial activity are discussed in this review.